Correlation of Interleukin-21 Levels With Clinical and Laboratory Parameters in ART Recipients - Meena, Manoj Kumar (Annals of Pathology and Laboratory Medicine, 2023)
Background: Interleukin-21 (IL-21) is a relatively new immune-enhancing, multifunctional and pleiotropic cytokine that plays an essential role in controlling chronic viral infections. It is a protein that in humans is encoded by IL-21 gene, mapped on chromosome 4 and 180 kb from IL-2 gene and the mRNA encoding the product is 616 nucleotides long. IL-21 is expressed in activated human CD4+ T cells but not in most other tissues. In addition, IL-21 expression is up-regulated by Th2 and Th17 subsets of T helper cells, as well as T follicular cells. Further IL-21 is expressed in NKT cells regulating the functions of these cells. IL-21 may be a critical factor in the control of persistent viral infections such as HIV. Present study aims to explore the levels of IL-21 in a select segment of ART recipients of East Delhi covered by NACP, Govt. of India. Methods: Estimation of levels of IL-21 was done using ELISA test employing commercially available kit (QAYEE-BIO Kit for Interleukin-21). The method of ELISA used for the present study was sandwich ELISA. Results: The mean levels of IL-21 in the study of 40 ART recipients were 1178.21Â±927.063. There were no controls included in the study. The range of IL-21 were 150-6100. In one patient IL-21 levels was not detected. Conclusion: This study attempts a clinical correlation with the levels of a cytokine with clinical and laboratory parameters which could help in a better understanding of the immunobiology of the disease. In the current study, the levels of IL-21 in samples of ART recipients were detected. A significant positive clinical correlation was seen between the levels of IL-21 and CD4 cell counts. IL-21 levels were high in those patients whose CD4 cell count was raised. There was a positive correlation between CD4 cell count and CRP. Therefore, further studies with a higher sample size may be required to arrive at a statistically significant correlation